Credit for low-income students and access to and academic performance in higher education in Colombia: a regression discontinuity approach (2015)
This study evaluates the impact of a national level subsidized loan program, ACCES, on a number of higher education outcomes (i.e., increase in enrollment rates, decrease in dropout rates, and increase in academic performance) of low-income students in Colombia. We use national level data along with a regression discontinuity design to estimate the impact of the program. The results confirm that the program was effective in terms of increasing the potential number of low-income students at the margin who would have enrolled in college, decreasing the number of students who dropped out, and increasing their academic outcomes.